(untitled) (UTM Press - Edited Book, 2025)
This book gathers chapters that mainly focus on the extraction of active compounds from plant based natural resources including herbal and fruit plants. Plants consist of many thousands of active compounds which can be beneficial for human health. People get the benefits of active compounds by formulating them into various products or bioproducts such as ethano-pharmaceutical, cosmetic, nutraceutical and/ or functional foods. The active compounds can be classified into two main sub-groups, either as primary metabolites or secondary metabolites. Primary metabolites mostly cover plant polysaccharides and proteins with a wide range of molecular weights. On the other hand, secondary metabolites can be further grouped into phenolics, flavonoids, terpenoids and alkaloids as the major constituents. However, the quantity of active compounds is very small from milligram to microgram, and therefore, the use of suitable extraction techniques and their optimized processing variables are important in order to obtain high yield of active compounds from the raw material of natural resources. Various advanced extraction technologies have been applied for extracting target compounds from various plant materials as described in the individual chapters. The chapters also provide the optimized variables for different extraction techniques in accordance with the nature of resources.